PEMANFAATAN BAKTERI HETEROTROF YANG DICAMPUR DALAM AIR UNTUK MENINGKATKAN KESEHATAN IKAN NILA SALIN (Oreochromis niloticus) - Ilham Fajri Pohan; Iesje Lukistyowati; F. Feliatra F. Feliatra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRAKThis research was conducted from March to June at the Laboratory of Fish Parasites and Diseases, the Marine Microbiology Laboratory and the Marine Chemistry Laboratory of the Faculty of Fisheries and Maritime Affairs, Riau University, Pekanbaru. The purpose of this study was to analyze the effectiveness of heterotrophic bacteria to improve water quality and body resistance of salted tilapia (Oreochromis niloticus) from haematological (Erythrocytes, hematocrit, hemoglobin and leukocytes) against disease.The method used in this study is an experimental method, using a Completely Randomized Design (CRD), 1 factor, namely with five levels of treatment three replications. Kn: Without administration of heterotrophic bacteria, without being tested, Kp: Without administration of heterotrophic bacteria, tested by Aeromonas hydrophilla bacteria, P1G: Giving heterotrophic bacteria Vagococus fluvialis at a dose of 15ml /25L, P2G: Giving heterotrophic bacteria Bacillus cereus at a dose of 15ml/25L, P3G: Provision of combined heterotrophic bacteria Bacillus cereus and Vagococus fluvialis at a dose of 15ml/25L. The results showed that the best treatment was P3 treatment using combined heterotrophic bacteriaBacillus cereus and Vagococus fluvialis. This is based on the value of blood parameters after the challenge test with Aeromonas hydrophila bacteria showing total erythrocytes of 252.33x104 cells/mm3, total leukocytes 90.13x103 cells/mm3, hemoglobin levels 8.03 g/dL, hematocrit 32.23%, survival rate 96, 66% and absolute weight growth of 4.82 g/head. The results of measurements of water quality during the study temperature range between 27-27.40C, dissolved oxygen 1.8-2.3 ppm, pH of water ranged from 7.8 to 7.9. Keywords: Heterotrophic Bacteria (B. Cereus and V. Fluvialis), Salted Tilapia (O. Nilloticus)